2020
DOI: 10.1186/s12913-020-4963-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, economic and organizational impact of pharmacist interventions on injectable antineoplastic prescriptions: a prospective observational study

Abstract: Background: Pharmacists play a key role in ensuring the safe use of injectable antineoplastics, which are considered as high-alert medications. Pharmaceutical analysis of injectable antineoplastic prescriptions aims to detect and prevent drug related problems by proposing pharmacist interventions (PI). The impact of this activity for patients, healthcare facilities and other health professionals is not completely known. This study aimed at describing the clinical, economic, and organizational impacts of PIs pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
10
1
3
Order By: Relevance
“…17 This allows the CLEO tool to be used for screening to select PIs for economic studies. This approach was used by Zecchini et al 18 in the setting of a cancer department to select PIs that induced positive and negative cost savings as part of their estimation of the total amount of money saved as a result of PIs.…”
Section: Original Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…17 This allows the CLEO tool to be used for screening to select PIs for economic studies. This approach was used by Zecchini et al 18 in the setting of a cancer department to select PIs that induced positive and negative cost savings as part of their estimation of the total amount of money saved as a result of PIs.…”
Section: Original Researchmentioning
confidence: 99%
“…The independence of three dimensions helps to interpret the scoring results flexibly. Mongaret et al 21 and Duwez et al 22 used only the clinical dimension of the CLEO tool in their study to determine clinically significant PIs, while Zecchini et al 23 used only the clinical and economic dimensions. Another tool could take advantage of all three dimensions to demonstrate the whole effects of a PI.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…19 The CLEO tool has been recently created according to different scales available in the literature 24 and provided suitable inter-rater and intrarater reliabilities. This CLEO tool was used to assess clinical impact of PIs on injectable antineoplastic prescriptions in a French Hospital Chemotherapy Preparation Unit 33 and was translated and validated in a German version. 34 We acknowledge that the use of a new tool adapted to clinical practice for assessing clinical impact of PIs does not allow any comparison with previous studies in several solid organ transplantation, 7 15 27 28 31 which mainly used Overhage and Lukes and Hatoum et al scales.…”
Section: Discussionmentioning
confidence: 99%
“…These actions include but are not limited to identifying and managing DRPs, ensuring better utilization of medications, to eventually reduce the risk of unfavorable ADEs, which in turn reduces the healthcare costs [8]. Indeed, previous studies reporting pharmacists' participation in the cancer setting have demonstrated improved quality of care [9][10][11]. However, recruiting clinical pharmacists as well as implementing the interventions themselves can come with added costs that may offset any cost savings produced by the prevention of ADEs.…”
Section: Introductionmentioning
confidence: 99%